Influenza vaccination among pregnant women: increasing awareness and coverage. (30th September 2020) - Carini, E; Bruno, S; Di Pilla, A; Beccia, V; Di Pumpo, M; Damiani, G; Carducci, B; Masini, L; Lanzone, A; Laurenti, P
Abstract: Influenza is a serious public health issue and pregnant women are one of the categories at higher risk of complications. Vaccination represents a safe and effective tool for prevention but the importance is not well perceived and the coverage is low (ECDC: 25% median in 2016/17). A program of education and free vaccination has been proposed to pregnant women following birthing classes. The aim was to increase pregnant awareness and to increase vaccination coverage of both parents. Classes about vaccinations, their timing and efficacy were given and a dedicated ambulatory operating twice a month during the flu season was set up. After the classes, the women were addressed to the ambulatory to be vaccinated. Vaccination was offered to the partners of the pregnant as well. General data, anamnesis and data about previous vaccinations were asked and then entered into a database. The number of women participating to the birthing classes from October 2019 to January 2020 was 119. Of those, from the beginning of the vaccination sessions on November 14th 2019 until January 16th 2020, 46 were vaccinated in the dedicated ambulatory (plus 2 in the resident ambulatory of the hospital). The compliance to vaccination was 40.34%. An additional number of 39 partners was also vaccinated. November was the month with the highest number of people vaccinated (20 women and 14 partners), while January had the lowest (7 women and 8 partners). As expected a higher number of people got vaccinated at the beginning of the flu season. A considerable number of partners decided to vaccinate, showing the parents understanding of the importance of herd immunity. Sensitising the women towards vaccination and increasing their awareness is crucial to improve women and new-borns' health status. Even though the compliance was considerable, a lot of work has to be done to improve vaccination coverage and to make the importance of vaccination clear. Key messages: Providing a programme of sensitisation could improve influenza vaccination coverage. The compliance, although satisfactory, can be further improved providing different and steady educational strategies.